2013
DOI: 10.1172/jci66218
|View full text |Cite
|
Sign up to set email alerts
|

AMPK dysregulation promotes diabetes-related reduction of superoxide and mitochondrial function

Abstract: Diabetic microvascular complications have been considered to be mediated by a glucose-driven increase in mitochondrial superoxide anion production. Here, we report that superoxide production was reduced in the kidneys of a steptozotocin-induced mouse model of type 1 diabetes, as assessed by in vivo real-time transcutaneous fluorescence, confocal microscopy, and electron paramagnetic resonance analysis. Reduction of mitochondrial biogenesis and phosphorylation of pyruvate dehydrogenase (PDH) were observed in ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
410
4
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 389 publications
(450 citation statements)
references
References 56 publications
32
410
4
4
Order By: Relevance
“…AICAR did not affect the total number of renal macrophages in the mouse model used, but rather shifted their phenotype towards resolution by reducing the percentage of CD11c + M1 macrophages. Collectively, this supports previous work from our group and others, demonstrating that AICAR attenuates both HFD-induced [12,13] and diabetes-induced [14,15] kidney disease. Importantly, in this study, we now also demonstrate that AICAR-mediated protection against kidney disease is independent of adiponectin.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…AICAR did not affect the total number of renal macrophages in the mouse model used, but rather shifted their phenotype towards resolution by reducing the percentage of CD11c + M1 macrophages. Collectively, this supports previous work from our group and others, demonstrating that AICAR attenuates both HFD-induced [12,13] and diabetes-induced [14,15] kidney disease. Importantly, in this study, we now also demonstrate that AICAR-mediated protection against kidney disease is independent of adiponectin.…”
Section: Discussionsupporting
confidence: 91%
“…In a subset of mice, dihydroethidium (DHE, 50 mg/kg) was administered by i.p. injection 16 h before the mice were killed to quantify renal superoxide levels by confocal imaging (n = 4 per group) [14]. Detailed protocols for liver function analysis, HPLC plasma creatinine analysis and renal superoxide measurements are described in ESM Methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Several studies indicate that the AMPK, PPARa, and PGC1a pathways are important in fibrosis development. 29,[48][49][50][51] Data from the Duffield group suggest that microRNA 21 is an important upstream regulator of the pathway. 52 In conclusion, this study showed that selective deletion of Lkb1 in the kidney induced severe injury over time, characterized by dilated tubules and interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The Brownlee hypothesis is an area of ongoing controversy and active investigation. A recent study has suggested that this excess of mitochondrial ROS may not be a universal finding [14], and there is increasing evidence of the importance of nonmitochondrial sources of ROS, including cytosolic production of ROS by NADPH oxidase [15]. Furthermore, although the polyol pathway has now been under active investigation for over 40 years, except for some limited data in neuropathy, agents that inhibit this pathway, such as aldose reductase inhibitors, have not been widely used in clinical practice.…”
Section: Mechanisms Of Complications: the Current Paradigmmentioning
confidence: 99%